DOES PROFITABILITY, FIRM SIZE, AND MACROECONOMIC VARIABLE AFFECT YIELD TO MATURITY OF CORPORATE SUKUK? - Utami, Suci Aprilliani; Rohmana, Yana (The International Journal of Business Review (The Jobs Review), 2019)
The purpose of of this research is to examine the influence of profitability, firm size, and macroeconomic variable on the yield to maturity of corporate sukuk. The yield to sukuk maturity that will be received by investors illustrates the level of investor profit but the yield level also describes the level of risk borne by investors. This research was conducted on all companies listed on the Indonesia Stock Exchange in the 2015-2018 period which issued sukuk ijarah and published its financial statements during the research period. The research samples is 54th ijarah sukuk This research was conducted using a quantitative approach with panel data. The data analysis technique used in this study is panel data regression with a fixed effect model. The results showed that profitability projected with Return on Asset did not affect the yield to maturity of sukuk ijarah, the size of the firm negatively affected the yield to maturity of sukuk ijarah, the BI-Rate variable had a positive and significant effect on yield to maturity of sukuk and inflation had a negative effect on yield of ijarah sukuk.